The Effect of TikTok Shop Feature Usage Intensity and Emotional Intelligence on Consumer Behavior Among Teenagers - Syaffira, Intan; Marwan, M Ravii (Universitas Pendidikan Nasional, 2024)
Online shopping has become a common activity for fulfilling consumer needs. Currently, TikTok Shop is one of the e-commerce platforms widely used by teenagers for online shopping. This study aims to examine the intensity of TikTok Shop usage and its impact on consumer behavior among teenagers through the TikTok Shop application. It also investigates the influence of the TikTok Shop feature and emotional intelligence on consumer behavior, and how these factors collectively account for 46.6% of the variation in consumer behavior, which is categorized as moderate. The study uses the 5% Slovin formula for sample size determination. The findings indicate that the intensity of using the TikTok Shop feature and emotional intelligence have a positive effect on consumer behavior among teenagers. Specifically, greater use of the TikTok Shop feature is associated with higher emotional intelligence, which in turn encourages consumer behavior in teenagers. Multiple linear regression analysis reveals that the intensity of TikTok Shop usage significantly influences emotional intelligence, which positively affects consumer behavior among adolescents.